Participation and third party involvement in mafia-related crime association: a liquid border (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The article focuses on the categorization of the conducts carried out by all the subjects who act in the so called “grey area”: conducts which lie between participation and joint liability as an external party. In particular, the issue relates to the difficulty to determine the defined boundaries between the “mafia” based conspiracy and the rules on the joint liability applied to the offence of conspiracy itself.The perspective of the work will be extremely empirical, except for some systematic order premises. A case study will be analyzed. Additionally, the results of an empirical research focused on the evolution of the activity on art 416-bis c.p. in the proceedings before the Public Prosecutor and the Court of Milan from 2000 to 2015 carried out by a group of University Bocconi will be presented and discussed.Key words: organized crime; covin; white-collar crime; empirical study; economy